Projectile Detecting Mechanism For Electromagnetic Launcher - Ismail, Noorasita (Universiti Teknologi Petronas, 2004)
Electromagnetic launcher is a device capable of launching projectile aimed at a location specified by the user. The sole purpose of a launcher is to fire a projectile, while for general application in physics and engineering; the launcher can also be used to carry out more complex functions including a broad range of military applications, the launch of aircraft into flight, the launch of objects directly into space and the acceleration of materials to extremely high velocities. In recent studies, most of launchers do not have the capability in realignment. By using a condenser microphone circuit, this paper presents the process to design or to measure the actual position of a projectile. In addition, Lab View software will be used as the controller for this sensing mechanism. This is actually a smart way to find the position of the projectile instead of using radar system, which requires a higher cost. Another application that can be relate with this projectile detecting mechanism is that it can be used in Olympics games especially in shot put games where this games required to detect the ball being thrown. The measurement can be further improved by replaced the old fashion measurement (using measuring tape) with this system.